Technologies for conservation and productivity: subtitutives or complementaries. - Sain, Gustavo (Agronomía Mesoamericana, 2016)
The increase of agricultural productivity and the conservation of natural resources are announced as desirable objectives of agricultural research. They are, however, frequently presented as substitutes. Reaching one it should make necessarily to coast of sacrificing the other. This work presents the idea that both objectives could be complementary to each other through the development and transfer of technologies that simultaneously enhance productivity and conserve resources (PERC technologies). This idea is illustrated with the case of conservation tillage wih crop residue managements. Finallu the work lists the costs and benefits of technologies that are available or that are in advanced stages of development in the region.